ON THE BASIS OF PERCEPTION: A MODERATED MEDIATION ANALYSIS OF DOING BUSINESS AND CORRUPTION - Muhammad Dahlan (Badan Pendidikan dan Pelatihan Keuangan - Kementerian Keuangan Republik Indonesia, 2022)
One of the landmark projects from the World Bank was the initiative called the Ease of Doing Business (EODB), which captures business regulatory settings in countries worldwide. The EODB scores have long indicated a country’s attractiveness in doing business with private sectors and have attracted many scholars, policymakers, and practitioners to explore. Many researchers have indicated that doing business scores were associated with economic growth, international relations, business development, and many other areas. This study contributes to the debate on how business regulations are associated with the perception of corruption index (CPI) using moderated mediation analysis. The results find that GDP per capita mediates the relationship between EODB and CPI and that country’s income category moderates the mediation. The relationships are explored for a period of ten years, from 2010 to 2019 worldwide (n= 146). The country’s income category moderated the mediating impact of GDP per capita by softening the influence of EODB on CPI ( .3013, BootSE = .0507, LLCI =0.2246, ULCI= 0.4226). The author suggests corroborating factor analysis and exploring the variables using more advanced path analysis for future research